DAMPAK PEMANENAN KAYU DENGAN TEKNIK REDUCED IMPACT LOGGING TERHADAP LIMBAH KAYU DI HUTAN ALAM TROPIKA - Muhdi Muhdi (Purifikasi, 2008)
The objective of this research was to determine the effect of forest harvesting caused by reduced impact logging (RIL) to wood residues. This research was carried out in a natural tropical forest of Ketapang, West Kalimantan. The result of the research showed that the volume of wood residues by conventional logging (CL) were 13.70 m3/ha (39.58 %) or the average of wood residues were 2.28 m3 from a tree felled. However, the volume of wood residues by reduced impact logging (RIL) were 11.059 m3/ha (24.70 %) or the average of wood residues were 2.08 m3 from a tree felled. The research indicated that the effect of forest harvesting to wood residues caused by RIL was lower than that of conventional logging (CL).